Pengaruh job crafting terhadap job satisfaction melalui work engagement sebagai variabel intervening - Kibtianingsih; Hadi, Hafid Kholidi (Jurnal Ilmu Manajemen, 2025)
This research aims to test and analyze the influence of Job crafting on Job satisfaction through work engagement as an intervening variable. This research uses quantitative methods. The sampling technique uses non-probability sampling with a census or total sampling type, where the entire population is sampled with 43 respondents. The statistical analysis used in this research is Structural Equation Model – Partial Least Square (SEM-PLS) with SmartPLS 3.2.9 software. The results of this research explain that job crafting has a positive and significant effect on job satisfaction. Job crafting has a positive and significant effect on work engagement. Work engagement has a positive and significant effect on job satisfaction. While in the analysis of the indirect effect of work engagement, it is able to mediate the influence of job crafting on job satisfaction. The implications of this study indicate that companies need to pay more attention to the development of job crafting as one of the key strategies in increasing employee work engagement and job satisfaction. Therefore, it is important to empower employees by proactively redesigning employee tasks, building constructive working relationships, and adopting a more positive perspective on work. So that it can strengthen employee emotional attachment to the organization, while creating a more productive work environment.